Preparation of nano-sized titanium carbide particles via a vacuum carbothermal reduction approach coupled with purification under hydrogen/argon mixed gas. Issue 15 (30th January 2017) - Xie, Zhen; Deng, Yi; Yang, Yuanyi; Su, Hua; Zhou, Dali; Liu, Can; Yang, Weizhong
Abstract : Nano-sized titanium carbide particles were successfully synthesized through a process of producing carbon coated titanium precursors, heating these precursors under vacuum conditions, and treating the products in hydrogen/argon mixed gas. Abstract : In the present work, nano-sized titanium carbide (TiC) particles were successfully synthesized through a process of producing carbon coated titanium precursors, heating these precursors under vacuum conditions at 1450 °C for 2 h, and treating the products in hydrogen/argon (1 : 1) mixed gas or hydrogen gas. The effects of carbon content, pressure and temperature of removing excess carbon on the TiC products were examined by using XRD, SEM, TEM and DTA-TG analysis. Experimental results demonstrated that TiC powders with a single phase were obtained when the molar ratio of Ti to C ranged from 1 : 2 to 1 : 4. With changing the molar ratio of Ti/C in the precursors, the particle size of the synthetized TiC powders varied from 30 to 200 nm. After treatment in the hydrogen/argon mixed gas at 830 °C for 3 h, the TiC product accounted for a high TiC purity of 99.36% and possessed a small grain size of about 20 nm. The vacuum calcination method coupled with the hydrogen/argon mixed gas process applied in this work would be an efficient way to obtain nano-sized and purified TiC particles, which hold great promising for industrial purposes.